Fixed-time event-triggered fault-tolerant formation-containment control for underactuated USVs with uncertain dynamics - Li, Junpeng; Fan, Yunsheng (Nonlinear dynamics, 2025)
This paper studies the problem of distributed fixed-time event-triggered formation tracking control for multiple underactuated unmanned surface vehicles (USVs) subject to actuator failures and input saturation. The system is guided by multiple virtual leaders moving along parameterized trajectories, while only a subset of the USVs can obtain information. To achieve the formation-containment control of USVs, an observer-based fixed-time control method is proposed. Specifically, the underactuated issue is addressed by redefining the system output via coordinate transformation, and an asymmetric saturation model is introduced to limit the control input. Subsequently, a fixed-time disturbance observer (FxTDO) is designed to estimate the composite disturbance in real time, including actuator failures, uncertain dynamics, and external disturbances. On this basis, a fixed-time controller combined with a relative threshold event-triggered mechanism is developed within a backstepping design framework. This approach ensures that the tracking errors converge within a fixed time while reducing the frequent actions of the actuators. Stability analysis demonstrates that all error signals in the closed-loop system remain ultimately uniformly bounded (UUB), guaranteeing that USVs achieve distributed formation within a fixed time while preventing Zeno behavior. Finally, the effectiveness of the proposed strategy is verified by simulation studies.